Child Refugees: Among the Fulfillment of the Right to Education and State Responsibilities - Dwi Hasya, Afifah (Uti Possidetis: Journal of International Law, 2023)
This article discusses the fulfillment of the educational rights of child refugees in Indonesia and Indonesia's responsibilities as a country that ratified the 1989 Convention on the Rights of the Child. Although until now the 1951 Convention on the Status of Refugees has not been ratified by Indonesia, refugees have long been coming to Indonesia as a transit country before refugees were placed in country of destination. Refugees who come to Indonesia are not only adults, but also children. A child refugee has the right to education, wherever and regardless of his or her nationality. The right to education for refugee children has been recognized in the Convention on the Rights of the Child. The results of this study indicate that in the CRC, every child who is seeking refugee status or has been officially designated as a refugee in a convention participating country is entitled to their rights, including their right to education. Indonesia as a participating country in the CRC has a responsibility in efforts to grant child refugee rights as stipulated in the CRC. However, in practice it is not fully carried out by the Government of Indonesia, because it is hampered by the absence of aÂ  legal protection, namely the 1951 Convention.